SKBDN Products: Implementation of Sharia Compliance in Bank Syariah Indonesia - Sokhikhatul Mawadah (AL-ARBAH: Journal of Islamic Finance and Banking, 2024)
Purpose - The aim of this research is to find out how BSI's sharia compliance applies to SKBDN (Domestic Letter of Credit) products.Method - This research is qualitative research. The data used is primary data originating from interviews with BSI employees. Secondary data was obtained from books, journals and previous research.Result - The results of the research state that the implementation of BSI Semarang City Sharia Compliance in SKBDN, namely BSI has implemented sharia compliance based on maqashid sharia, including: 1). Ad-dien: BSI is guided by the Koran, Hadith and other Islamic laws in carrying out all its operational systems and products. 2). an-nafs: SKBDN services involve several parties, including customers, BSI and goods providers. This is where it is important for the parties to be trustworthy. 3). al-aql: BSI participates in educating customers (provides education on every bank product to customers through seminars and training). 4). an-nasl: caring for offspring, BSI guarantees that customer funds come from halal funds which have a good impact on the family and descendants and 5). al-mal: BSI takes profit from the services of implementing SKBDN services through fees charged.Implication - This research explores Islamic values, with sharia maqashid indicators in sharia banking, especially in SKBDN products. It is hoped that service in sharia banking will be better and more customers (applicants) will choose SKBDN products in sharia banking.Originality - This article examines sharia compliance of sharia banks using the maqashid sharia approach. SKBDN applicants are more aware and comfortable choosing SKBDN services in sharia banking.